(untitled) (Лучшие интеллектуальные исследования, 2025)
Antibiotics play a vital role in dental practice for managing orofacial infections. They are used to manage existing infection and they are also used as prophylaxis for certain medical conditions and surgical procedures. This article will review pharmacological and therapeutic considerations for the proper use of these agents for dental infections. An astounding number of drug classes and formulations are available to manage infections. Fortunately, the microorganisms associated with odontogenic and periodontal infections are well characterized and a relatively small number of antimicrobial agents are required to effectively manage dental infections. With the exception of allergy, adverse effects attributed to these antibiotics are surprisingly infrequent, but most agents are implicated in producing nausea, dyspepsia, and diarrhea. This article will review essential pharmacology of appropriate drug classes and then address clinical considerations for their therapeutic and prophylactic use.